Energy, Ecology, and Climate Finance Issues on Eve of COP29 - Gubad Ibadoghlu (ZBW - Leibniz Information Centre for Economics, 2024)
This article examines the challenges Azerbaijan faced on the Eve of COP29. Assessing the situation in Azerbaijan regarding energy, ecology, and climate finance issues, the author systematizes the critical problems to be solved in this field and draws attention to Azerbaijan's policy on the Eve of COP29.
Keywords: 330; COP29; Azerbaijan; oil; gas; energy; ecology; climate change; climate finance; green growth; environmental security